Tax Salience, Voting, and Deliberation - Rupert Sausgruber; Jean-Robert Tyran (University of Innsbruck, Department of Public Finance, 2009)
Tax incentives can be more or less salient, i.e. noticeable or cognitively easy to process. Our hypothesis is that taxes on consumers are more salient to consumers than equivalent taxes on sellers because consumers underestimate the extent of tax shifting in the market. We show that tax salience biases consumers' voting on tax regimes, and that experience is an effective de-biasing mechanism in the experimental laboratory. Pre-vote deliberation makes initially held opinions more extreme rather than correct and does not eliminate the bias in the typical committee. Yet, if voters can discuss their experience with the tax regimes they are less likely to be biased.
Keywords: C92; H22; D72; 330; Tax salience; learning; deliberation; voting; Verbrauchsteuer; Steuertarif; Steuerinzidenz; Lernprozess; Test